Food Security Status in Agroforestry Landscapes of Way Betung Watershed, Indonesia and Molawin Dampalit Sub Watershed, Philippines - Christine Wulandari; Leila Dimayuga Landicho; Rowena Esperenza Dicolen Cabahug; Romnick Salvago Baliton; Irwan Sukri Banuwa; Susni Herwanti; Pitojo Budiono (Institut Pertanian Bogor (IPB University), 2019)
Indonesia and Philippines are homes of biodiversity in Southeast Asia. In recent years, however, there has been a decline in biodiversity brought about by land use change. This condition poses threat on the food security of communities around the watersheds. The type and volume of main food items depend on the ecological and physiological conditions of the watersheds, in this case, Way Betung and Molawin Dampalit. When edible food is sufficient and available in an area, there is higher livelihood that the communities are food secured. This paper argues based on research which has been conducted in May to November 2015 that the food security of communities in the selected agroforestry landscapes in Way Betung and Molawin Dampalit have moderate. Levels of its food security based on four dimensions, namely: food availability, food accessibility, food stability and food utilization. Amounted 261 Indonesia farmer’s respondents and 106 Philippine’s respondents mentioned that the farm households generally practice agroforestry where the production of short-term and medium-term agricultural crops, woody perennials and livestock are deliberately combined. The type of crops grown by the farm households contribute to the level of food security.